x2-5x-36=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -36 and whose sum is -5.

-9,4

Write the factored form using these integers.

(x-9)(x+4)=0

(x-9)(x+4)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-9=0

x+4=0

Set the first factor equal to 0.

x-9=0

Add 9 to both sides of the equation.

x=9

x=9

Set the next factor equal to 0.

x+4=0

Subtract 4 from both sides of the equation.

x=-4

x=-4

The final solution is all the values that make (x-9)(x+4)=0 true.

x=9,-4

Solve using the Square Root Property x^2-5x-36=0